The "highway effect" on public finance: Case of the STAR highway in the Philippines - Naoyuki Yoshino; Victor Pontines (Asian Development Bank Institute (ADBI), 2015)
In this study, we examine the impact of the STAR highway located in Batangas province, Philippines, on the public finance of the cities and municipalities through which it directly passes. Specifically, we exploit a unique, disaggregated dataset on tax (property and business taxes) as well as non-tax revenues (regulatory fees and user charges) of the cities and municipalities in the Batangas province. We find, based on our two specifications of a modified difference-in-difference model, that the STAR highway had a robust, statistically significant, and economically growing impact on business taxes. We also find that this so-called "highway effect" also extends to municipalities located in a neighboring province to Batangas. Furthermore, based on more careful inspection and robustness checks, it appears that the STAR highway had a significant impact not only on business taxes, but also on property taxes and regulatory fees. These findings support the widely held belief that infrastructure investments matter; further, our micro-case study suggests that infrastructure investments can indirectly boost tax and non-tax revenues through their power to reduce transportation costs and enhance the activity of firms and workers located along the highway.
Keywords: H54; H71; O22; R11; 330; Infrastructure investment; public finance; STAR highway